TEMPORAL TRENDS IN FISHING GEAR COMPOSITION AND FLEET MODERNIZATION IN EAST NUSA TENGGARA 2019–2024 - Joi Alfreddi Surbakti; Alexander S. Tanody (Universitas Mataram, 2026)
East Nusa Tenggara (NTT) is one of Indonesia's most biologically productive fishing zones, yet its capture fisheries sector has experienced a sustained contraction in gear deployment over the 2019–2024 period. This study analyzes temporal trends in fishing gear composition and fleet structure across all 22 regencies using an integrated provincial dataset of 3,919 gear-observation records. Province-wide gear counts fell from 59,161 units in 2019 to 29,960 units in 2024 a decline of 49.4%. A Pettitt change-point test places the structural break between 2021 and 2022, consistent with the regulatory and economic disruptions of that period. A negative binomial regression confirms that year, regency, vessel size class, and water type are all significant predictors of gear count. Shannon diversity indices show a sharp contraction in gear portfolio breadth (mean H' from 1.74 in 2019 to 1.55 in 2024), with substantial inter-regency heterogeneity. Ward's hierarchical clustering identifies four distinct fleet archetypes: gill-net–dominant, line-gear dominant, mixed-gear transitional, and trap-based coastal systems. Non-motorized boat gear declined by 60.4%, while medium-class vessels (21–30 GT) expanded by 339%. The findings indicate a structural shift toward motorized, selective gear systems, with implications for sustainable management, effort licensing, and spatial planning in eastern Indonesian waters.